The Toxicology Investigators Consortium 2023 Annual Report - Adrienne Hughes; Alexandra Amaducci; Sharan L. Campleman; Shao Li; Mari Costantini; Meghan B. Spyres; Hannah Spungen; Jessica Kent; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; et al. (Journal of Medical Toxicology, 2024)

Early life exposure to mercury and relationships with telomere length and mitochondrial DNA content in European children - Manuel Lozano; Rosemary R.C. McEachan; John Wright; Tiffany C. Yang; Courtney Dow; Manik Kadawathagedara; Johanna Lepeule; Mariona Bustamante; Lea Maitre; Martine Vrijheid; Anne Lise Brantsæter; Helle Margrete Meltzer; et al. (Science of The Total Environment, 2024)

Effects of management objectives and rules on marine conservation outcomes - Natalie C. Ban; Emily S. Darling; Georgina G. Gurney; Whitney Friedman; Stacy D. Jupiter; W. Peni Lestari; Irfan Yulianto; Sinta Pardede; Sukma A. R. Tarigan; Puji Prihatiningsih; Sangeeta Mangubhai; Waisea Naisilisili; et al. (Conservation Biology, 2023)
Understanding the relative effectiveness and enabling conditions of different area‐based management tools is essential for supporting efforts that achieve positive biodiversity outcomes as area‐based conservation coverage increases to meet newly set international targets. We used data from a coastal social–ecological monitoring program in 6 Indo‐Pacific countries to analyze whether social, ecological, and economic objectives and specific management rules (temporal closures, fishing gear‐specific, species‐specific restrictions) were associated with coral reef fish biomass above sustainable yield levels across different types of area‐based management tools (i.e., comparing those designated as marine protected areas [MPAs] with other types of area‐based management). All categories of objectives, multiple combinations of rules, and all types of area‐based management had some sites that were able to sustain high levels of reef fish biomass—a key measure for coral reef functioning—compared with reference sites with no area‐based management. Yet, the same management types also had sites with low biomass. As governments advance their commitments to the Kunming–Montreal Global Biodiversity Framework and the target to conserve 30% of the planet's land and oceans by 2030, we found that although different types of management can be effective, most of the managed areas in our study regions did not meet criteria for effectiveness. These findings underscore the importance of strong management and governance of managed areas and the need to measure the ecological impact of area‐based management rather than counting areas because of their designation.

A probabilistic seismic hazard assessment for Wylfa Newydd, a new nuclear site in the United Kingdom - Manuela Villani; Zygmunt Lubkowski; Matthew Free; Roger M. W. Musson; Barbara Polidoro; Rory McCully; Areti Koskosidi; Crispin Oakman; Tim Courtney; Martin Walsh (Bulletin of Earthquake Engineering, 2020)

Understanding the evolving phenotype of vascular complications in telomere biology disorders - Cecilia Higgs; Yanick J. Crow; Denise M. Adams; Emmanuel Chang; Don Hayes; Utz Herbig; James N. Huang; Ryan Himes; Kunal Jajoo; F. Brad Johnson; Susan D. Reynolds; Yoshihiro Yonekawa; et al. (Angiogenesis, 2019)

A sperm whale's perspective: The importance of seasonality and seamount depth - Courtney H. Hann; Tim D. Smith; Leigh G. Torres (Marine Mammal Science, 2016)

Comparing Chemistry and Census-Based Estimates of Net Ecosystem Calcification on a Rim Reef in Bermuda - Travis A. Courtney; Andreas J. Andersson; Nicholas R. Bates; Andrew Collins; Tyler Cyronak; Samantha J. de Putron; Bradley D. Eyre; Rebecca Garley; Eric J. Hochberg; Rodney Johnson; Sylvia Musielewicz; Tim J. Noyes; et al. (Frontiers in Marine Science, 2016)

A missense mutation in LRR8 of RXFP2 is associated with cryptorchidism - Rebecca M. Harris; Courtney Finlayson; Jeffrey Weiss; Lisa Fisher; Lisa Hurley; Tim Barrett; Donna Emge; Ross A. D. Bathgate; Alexander I. Agoulnik; J. Larry Jameson (Mammalian Genome, 2010)

Abstracts of the 6th FECS Conference 1998 Lectures - F. Sherwood Rowland; Donald R. Blake; B. R. Larsen; Anne Lindskog; Peter J. Peterson; W. Peter Williams; T. J. Wallington; M. J. Pilling; N. Carslaw; D. J. Creasey; D. E. Heard; P. Jacobs; et al. (Environmental Science and Pollution Research, 1998)